CALL IT BY ITS NAME: A PARTIAL GLOSSARY ABOUT SEXUAL HARASSMENT FOR FACULTY MEMBERS - Hurren, Wanda (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
This partial glossary of words and phrases expands awareness regarding sexual harassment occurring among faculty members, to encourage a culture of not keeping secrets about sexual harassment. Media attention has shed light on the levels of sexual harassment faced by students in higher education, yet silence surrounds levels of harassment faced by faculty members, and this is a phenomenon that also affects students and learning. Intersectionality and the influence of power dynamics in higher education are acknowledged as mitigating factors in cases of sexual harassment. Structural aspects of higher education that enable a “secrets code” are outlined, along with possible strategies to both reduce and report incidents of sexual harassment.